Study on situation to overcome the consequences of toxic chemicals to humans in Cam Lo District, Quang Tri province : Luận văn ThS. Khu vực học: 60 31 60 - Dương, Thị Vân Anh (Viện Việt Nam học và Khoa học Phát triển, 2017)
102 p. + CD-ROM